Law and emerging issues : proceedings of the International Conference on Law and Emerging Issues (ICLEI 2023) - International Conference on Law and Emerging Issues (2023 : School of Law, AURO University); Sharma, Shilpi; Mukherjee, Baidya nath (Abingdon, Oxon ; New York, NY : Routledge, Taylor & Francis Group, 2024)
In the ever-evolving landscape of law and governance, adaptation and innovation are key to addressing the challenges of our times. This edited volume is a testament to the ever-evolving nature of the legal field and the ongoing efforts of legal scholars and academicians to dissect, analyze, and grapple with the challenges and opportunities presented by these changes. The topics covered in this book span a wide spectrum of legal domains, reflecting the complex and rapidly changing nature of our contemporary world. From corporate governance structures to emerging challenges in the digital space, from analyzing the implications of the Social Security Code 2020 in India to understanding the legal developments surrounding unorganized migrant workers during the COVID-19 pandemic, the breadth of subjects addressed here is both impressive and vital.
1. Interdisciplinary Approach to Corporate Governance Structure 2. Regulating Anticompetitive Practices with Reference to the Digital Space: A Comparative Study 3. Decoding Business Environment: Company's Perspective 4. Critical Analysis of the Social Security Code 2020 in India: Assessing Its Implications and Challenges 5. Issues of Unorganised Migrant Workers during COVID-19 Pandemic under Indian Legal and Judicial Developments 6. Arbitration Under Bilateral Investment Treaties: An Indian Perspective 7. A Study of Socio-Political Determinants of NOTA 8. Influence of International Environmental Norms in Domestic Laws: Indian Experience 9. Green Collar Crime - A Quest for Environmental Criminal Jurisprudence 10. Examining the Role of the Supreme Court in Imparting Environmental Justice in India while Implementing the Polluter Pays Principle 11. Legal Construction of Human Rights Jurisprudence and Judicial Gerrymandering: An Overview 12. Stereotyping and Gender Dynamics: Portrayal of Women in the Bollywood Films and Crimes of Stalking and Sexual Harassment 13. Gender Stereotyping in Media: Creating a Hurdle in the Socio-Legal Framework for Gender Mainstreaming 14. The Accountability of Stakeholders in Combating Domestic Violence with Women in India 15. Advancing Women's Health and Dignity: A Comprehensive Analysis of Menstrual Health Management and Rights in India 16. Breaking Barriers: The Power of Cyber Feminism in Combating Revenge Porn 17. Facial Recognition? An Analysis of Facial Recognition and Criminal Justice in India 18. Artificial Intelligence: The Modern Panopticon
Keywords: Law -- Congresses; LAW / General; LAW / Environmental; LAW / International